Rapid Holocene deposition in the Mackenzie Trough and Barrow Canyon areas in the western Arctic Ocean - Masanobu Yamamoto; Kenta Suzuki; Masafumi Murayama; Laura Gemery; Koji Seike; Leonid Polyak; Young Jin Joe; Shoma Uchida; Minoru Kobayashi; Jonaotaro Onodera; Keiji Horikawa; Yuhji Yamamoto; et al. (Progress in Earth and Planetary Science)
Abstract The Arctic Ocean and terrestrial environment have recently been reported to be changing drastically, but it is unclear whether these changes are similar to natural variations in the past or how sudden and large the changes are compared to natural variations. This premise served as motivation to collect sediment cores during the summer of 2022 at four sites on the Canadian continental shelf and Alaskan upper continental slope to reconstruct changes in the marine and terrestrial environments to provide a comprehensive picture of the ocean environment during the preindustrial period before anthropogenic influences. We dated the sediments based on the 137Cs radioactivity of bulk sediments and the 14C concentrations of mollusk shells. The 137Cs radioactivity shows a distinct onset corresponding to 1950 Common Era (CE) and the most prominent peak corresponding to 1963 CE. Multiple peaks appeared above the most prominent one, coinciding with nuclear power plant accidents in 1986 and 2011. Inventories of excess 210Pb in all cores exceed the estimated supply of excess 210Pb from atmospheric deposition, likely due to the scavenging supply of excess 210Pb. By comparing 137Cs and radiocarbon conventional ages, we estimated the local radiocarbon reservoir age value of each site. Using these local radiocarbon reservoir age and the conventional ages of mollusk shell samples, we established the age-depth models by the Bayesian method. The optimal ΔR values were 598, 511, 65, and –60 years at the MT1, MT2, BC2, and BC2-2 sites, respectively. The cores consist of clayey silts continuously deposited with uniquely high sedimentation rates of 0.17 to 0.74 cm y−1. Variation in the Ca/Ti ratio indicates ~ 20, ~ 30, 50–60, 100–125, and 300-year cycles, likely attributed to the variation in the Aleutian Low that controls the Bering Strait inflow of Pacific waters influencing our core sites. These sediments will be used for further high-resolution, multi-proxy studies with forthcoming results.